Engaging parents in digital sexual and reproductive health education: evidence from the JACK trial - Áine Aventin; Aisling Gough; Theresa McShane; Kathryn Gillespie; Liam O'Hare; Honor Young; Ruth Lewis; Emily Warren; Kelly Buckley; Maria Lohan (BMC, 2020)
Abstract Background Research evidence and international policy highlight the central role that parents play in promoting positive sexual behaviour and outcomes in their children, however they can be difficult to engage in sexual and reproductive health (SRH) education programmes. Digital health promotion that uses online and mobile technologies (OMTs) to promote parent-child communication may offer an innovative solution to reach parents, however, few programmes have used OMTs to involve parents in SRH, and none have reported lessons learned in relation to optimising engagement. This study addresses this gap in the literature by reporting acceptability and feasibility of using OMTs to engage parents in SRH education. Findings will be relevant for those wishing to develop and implement digital SRH programmes with parents internationally. Methods The Jack Trial is a UK-wide cluster randomised controlled trial recruiting over 8000 adolescents from 66 socially and religiously diverse post-primary schools. An embedded mixed-methods process evaluation explored user engagement with parent components of the If I Were Jack SRH education programme, which include online animated films and a parent-teen homework exercise. Results A total of 109 adolescents, teachers, parents and SRH policy experts took part in semi-structured interviews and focus groups, 134 parents responded to an online survey, and 3179 adolescents completed a programme engagement and satisfaction questionnaire. Parents who accessed the materials were positive about them; 87% rated them as 'good or excellent' and 67% said they helped them have conversations with their child about SRH. Web analytics revealed that 27% of contacted parents accessed the digital materials, with 9% viewing the animated films. Only 38% of teachers implemented the homework exercise, mainly because they assumed that students would not complete it or it might result in backlash from parents. Conclusions While digital parental materials show promise for engaging parents in SRH education, this study suggests that in order to optimise engagement, parental components that give parents the necessary skills to have conversations with their children about sex should be coupled with efforts to increase school and teacher confidence to communicate with parents on sensitive topics. Trial registration ISRCTN99459996 .